Implementation of Transformational Leadership Styles in High School (SMA) During the Covid-19 Pandemic - Mulyani Mulyani; Betri Syafrina; Syufiarma Marsidin; Demina Demina (al-fikrah: Jurnal Manajemen Pendidikan, 2021)
Leadership plays an important role in realizing the vision and mission of educational institutions. Various models of suitable leadership styles can be adopted and applied by a school principal at the educational institution he leads. During the Covid-19 pandemic, a leader needs to apply the right leadership style. The transformational leadership style in high school (SMA) is quite ideal to be applied during the Covid pandemic. Transformational leadership has a close meaning with charismatic and vision, because by definition it focuses on change and transformation. Transformational leadership has four characteristics known as the 4Is, namely Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individual Consideration. Transformational leadership style has a significant and positive influence to bring about change. This leadership style is one of the leadership styles that can be implemented in high school during the Covid-19 pandemic.